Acetaminophen micropollutant: Historical and current occurrences, toxicity, removal strategies and transformation pathways in different environments. (December 2019) - Phong Vo, Hoang Nhat; Le, Gia Ky; Hong Nguyen, Thi Minh; Bui, Xuan-Thanh; Nguyen, Khanh Hoang; Rene, Eldon R.; Vo, Thi Dieu Hien; Thanh Cao, Ngoc-Dan; Mohan, Raj
Abstract: Acetaminophen (ACT) is commonly used as a counter painkiller and nowadays, it is increasingly present in the natural water environment. Although its concentrations are usually at the ppt to ppm levels, ACT can transform into various intermediates depending on the environmental conditions. Due to the complexity of the ACT degradation products and the intermediates, it poses a major challenge for monitoring, detection and to propose adequate treatment technologies. The main objectives of this review study were to assess (i) the occurrences and toxicities, (2) the removal technologies and (3) the transformation pathways and intermediates of ACT in four environmental compartments namely wastewater, surface water, ground water, and soil/sediments. Based on the review, it was observed that the ACT concentrations in wastewater can reach up to several hundreds of ppb. Amongst the different countries, China and the USA showed the highest ACT concentration in wastewater (≤300 μg/L), with a very high detection frequency (81–100%). Concerning surface water, the ACT concentrations were found to be at the ppt level. Some regions in France, Spain, Germany, Korea, USA, and UK comply with the recommended ACT concentration for drinking water (71 ng/L). Notably, ACT can transform and degrade into various metabolites such as aromatic derivatives or organic acids. Some of them (e.g., hydroquinone and benzoquinone) are toxic to human and other life forms. Thus, in water and wastewater treatment plants, tertiary treatment systems such as advanced oxidation, membrane separation, and hybrid processes should be used to remove the toxic metabolites of ACT. Graphical abstract: Image 103416 Highlights: China and the USA showed the highest acetaminophen (ACT) concentration. Advanced oxidation processes (AOPs) removed ACT to the ppt level. More than 20 by-products and intermediates of ACT were detected. Treated wastewater was not totally free from the toxic effects due to ACT metabolites.